ANALISIS PENGARUH PERUBAHAN PANJANG SPACER TERHADAP TORSI SEPEDA MOTOR 110 cc: ANALYSIS OF THE EFFECT OF SPACER LENGTH CHANGES ON TORQUE MOTORCYCLE 110 cc - Ficky Yuwan Dirta; Firdaus, Ahmad Hanif (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
As the age of a vehicle increases, the performance of its 110 cc automatic transmission engine tends to decline. This decline in performance becomes especially noticeable when less of responsive or attempting to navigate uphill terrains. Consequently, it becomes necessary to take measures to enhance the torque of the motorcycle. One such measure involves replacing the spacer length. This study aims to investigate the impact of spacer length adjustments on torque. The research methodology employed was experimental, involved variations in spacer lengths of 37.5 mm, 38.5 mm, and 40.0 mm. The findings reveal that the highest torque of 30.1 N.m was achieved with the 37.5 mm spacer, whereas the 38.5 mm spacer yielded a torque of 27.9 N.m, and the 40.0 mm spacer resulted in a torque of 23.8 N.m.